MULTIFREQUENCY PHASE METHOD OF RANGE MEASUREMENTS - O. N. Shinkaruk; V. R. Liubchyk; M. O. Lantvoit (Приборы и методы измерений, 2015)
The results of development of multi-frequency phase method of measuring distances are shown. The results of the passage of harmonic probing signals in probing the objectives are shown. Obtaining the mathematical model describing the relationship are shown. The mathematical transformation of the system of equations relating the complex amplitudes of the sum harmonic signals and complex amplitudes of the signals reflected from each object, the result of which there is a polynomial equation to obtain. Solution of the polynomial equation gives the values of the vectors of the signals which reflected from each goal.